AGES AND ORIGIN OF THE EARLY DEVONIAN GRANITES FROM THE NORTH PART OF CHINESE ALTAI MOUNTAINS AND ITS TECTONIC IMPLICATIONS - Tong Y.; Wang T.; Hong D.W.; Dai Y.J.; Han B.F.; Liu X.M. (My University, 2007)
Zircon U-Pb (LA-ICPMS) dating yields the 206Pb/238U ages of 398 ±5Ma(MSWD=2.3) and 399 ± 4(MSWD =1.2) for the Kanasi and Qiongkur granite plutons from the north part of the Chinese Altai Mountains, respectively. The results, combing with previously published data, show that the 400Ma ca. granitoids distribute widely in the Chinese Altai, and this period is a very important granitoids formation stage. The Kanasi, Qiongkur and other 400Ma ca. granites are enriched in K, Al, REE and LILE (Rb, K, Ba) with negative anomaly in Nb, Ta, Sr, Ti and P, and have negative εNd(t) values (- 1.5 - -0.5) and older tDM (1.15-1.35Ga) in relation to other granitoids in this area, which suggest that the granitoids mainly follow calc-alkaline and high-K calc-alkaline trends, form in continental are settings, and the sources of the granitoids contain both old continental and mantle-derived rocks. These features are the same as those of 400Ma ca. granitoids recognized from the central and southern Chinese Altai. All of these provide the new evidences for the seduction and accretion processes of the Chinese Altai in early-middle Paleozoic.
Keywords: ALTAI; EARLY PALEOZOIC; GEOCHEMISTRY; GRANITE; ZIRCON U-PB AGE; Devonian; Paleozoic::Devonian; Палеозой::Девонская